2016
DOI: 10.3390/su8090935
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Empirical Approaches to the Concept of Resilience: A Critical Examination of Panarchy, Ecological Information, and Statistical Evidence

Abstract: Despite its ambiguities, the concept of resilience is of critical importance to researchers, practitioners, and policy-makers in dealing with dynamic socio-ecological systems. In this paper, we critically examine the three empirical approaches of (i) panarchy; (ii) ecological information-based network analysis; and (iii) statistical evidence of resilience to three criteria determined for achieving a comprehensive understanding and application of this concept. These criteria are the ability: (1) to reflect a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Resilience is difficult to quantify (Kharrazi et al, 2016); however, it has been shown that some range of intermediate values is desirable in order to keep the state of a given SES in a region of high, and ideally maximum, sustainability (Goerner et al, 2015) while also considering the caveats noted by Benson and Craig (2014) on the evolution of the concept of sustainability over time. Therefore, resilience is a pre-condition for sustainability, although it is not itself a suitable foundation for a desired normative approach.…”
Section: A Pathway To Address Current Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience is difficult to quantify (Kharrazi et al, 2016); however, it has been shown that some range of intermediate values is desirable in order to keep the state of a given SES in a region of high, and ideally maximum, sustainability (Goerner et al, 2015) while also considering the caveats noted by Benson and Craig (2014) on the evolution of the concept of sustainability over time. Therefore, resilience is a pre-condition for sustainability, although it is not itself a suitable foundation for a desired normative approach.…”
Section: A Pathway To Address Current Challengesmentioning
confidence: 99%
“…In a single-scale problem, the adaptive cycle was applied to study the historical development of a National Forest in Alaska (Beier et al, 2009). Recently, Kharrazi et al (2016) presented several advantages of the panarchy approach for addressing resilience issues when compared to the Ecological Information and Statistical Evidence approaches.…”
Section: Internal Organization: the Panarchy Modelmentioning
confidence: 99%
“…Since both resource managers and stakeholders may only notice a state change when valued ecosystem traits or components are lost, a social–ecological approach to state identification may be inherently normative (i.e. values‐based) (Batavia & Nelson ; Davidson et al ; Kharrazi et al ), although resilience is considered rather to be descriptive by many authors (e.g. Derissen et al ) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…That is, success is value‐laden and these values must be acknowledged explicitly when assessing project outcomes (Batavia & Nelson ). Each manager must redefine resilience for each project (Kharrazi et al ). This means that managers may measure resilience as convenient to their existing projects and priorities.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its growing importance, the concept of resilience remains vague, on one hand hindering consistent meaningful application [9], while on the other hand, expanding its creative and trans-disciplinary scope [10]. The definition of the concept of resilience is influenced by one's disciplinary framework, socio-economic setting, and work experience [11]. While there are many definitions and measurements of resilience, a consensus among individual perspectives may be better achieved by understanding the common misconceptions of the concept.…”
Section: Introductionmentioning
confidence: 99%